Sosialisasi Literasi Digital dalam Upaya Pengembangan Keterampilan Profesionalisme Guru pada Yayasan Pesantren Ash-Shadiqi Sumenep Madura - Hidayati, Syafaatul; Hidayat, Ahmad; Rahman, Arip (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PkM) aims to describe the implementation of the digital literacy outreach program for teachers at the Ash-Shadiqi Islamic Boarding School Foundation in Sumenep and to analyze its impact on enhancing teacher professionalism. The program was carried out in five stages: preparation, socialization, training, mentoring, and evaluation. Initially, most teachers had low to moderate levels of digital literacy, but the training succeeded in improving technical skills, self-confidence, and collaboration. Evaluation results showed a 35% increase in technological understanding, and 80% of teachers were able to create their own digital teaching media. Despite encountering challenges, collaborative solutions effectively addressed them. This program not only strengthened technical skills but also fostered a digital learning community grounded in pesantren values.